2016
DOI: 10.5812/pedinfect.36539
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Privacy in Pediatric Wards in Teaching Hospitals Affiliated to Shahid Beheshti University of Medical Sciences: 2014 - 2015

Abstract: Background: Patients' privacy is an important ethical responsibility in medicine and an inseparable part of treatment. Children's privacy is no exception. Children's rights to privacy are recognized under the Children's Rights Convention as part of good medical practice. Objectives: Few studies have examined children's privacy in Iran or in other countries. Thus, the present study was designed to investigate views expressed by relatives who accompanied sick children to the hospital about various aspects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Davidson 44 suggested that staff assess family privacy concerns when conducting family presence on rounds. Foroozadeh et al, 21 in a study of the privacy of hospitalized children in paediatric units, reported that healthcare providers do care for patient confidentiality, but they pay less attention to physical confidentiality in young children. In the study, it was determined that paediatric nurses observed the patient's privacy, especially physical privacy most of the time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Davidson 44 suggested that staff assess family privacy concerns when conducting family presence on rounds. Foroozadeh et al, 21 in a study of the privacy of hospitalized children in paediatric units, reported that healthcare providers do care for patient confidentiality, but they pay less attention to physical confidentiality in young children. In the study, it was determined that paediatric nurses observed the patient's privacy, especially physical privacy most of the time.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, their right to privacy is often ignored. 21 Previous research has shown that a child’s need for privacy is associated with the development of a sense of independent identity. It has also demonstrated that children’s awareness of their environment and privacy and the need to have control over their own private space increases with age and cognitive development.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations